Histone H1 deposition and histone-DNA interactions in replicating chromatin. - Bavykin, S (1993)
An immunochemical method for analyzing protein interactions with BrdUrd-substituted DNA was used to study binding of histones to nascent DNA in nuclei. The results indicate that in Ehrlich ascites tumor (EAT) cells, histone H1 deposits on newly replicated DNA simultaneously with or immediately after core histone deposition so that in chromatin replicated for 3 min, the stoichiometry of the histones is the same as in bulk chromatin. All histones, and especially histone H1, interact with nascent DNA more weakly than with bulk chromatin, although the efficiency of interaction via the globular domains seems to be the same for both types of chromatin.